Acute Epstein-Barr virus-related myocarditis: life-threatening complication in immunocompetent patient - Kothia, Darpan P.; Rabadia, Priyanka J.; Patel, Bhaumikkumar M.; Makwana, Prakash V. (International Journal of Research in Medical Sciences, 2024)
Acute Epstein-Barr virus (EBV) related myocarditis is an uncommon but potentially life-threatening condition, particularly in immunocompetent individuals. We present a case of a 14-year-old male with no prior medical history who presented with high-grade fever, sore throat, and dyspnea on exertion. Laboratory tests and echocardiography confirmed the diagnosis of myocarditis secondary to EBV infection. The patient required conservative treatment. Follow-up at post-discharge revealed complete recovery, with normal echocardiographic findings and no residual symptoms. This case underscores the importance of early recognition and intervention in EBV-related myocarditis. Despite its rarity, clinicians should consider viral myocarditis in patients with systemic EBV infection and cardiac symptoms. Aggressive supportive care can lead to full recovery, as demonstrated by this case. It can present as a dengue-mimic.